Epidemiological Profile of Syphilis Patients at Secondary Hospital: A Two-Year Retrospective Study in the Dermatology and Venereology Outpatient Clinic - Christine Suryani Novelita Sutrisno; Desy Hinda Pramita; Ita Puspita Dewi (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Syphilis remains a re-emerging global health challenge, disproportionately affecting sexually active individuals in low- and middle-income countries. Despite effective diagnostic and treatment options, the disease continues to impose a high burden on key populations. In Indonesia, hospital-based epidemiological data remain limited, particularly from dermatology and venereology outpatient clinics where syphilis is commonly diagnosed and managed. Purpose: This study aimed to describe the epidemiological profile of syphilis patients attending the Dermatology and Venereology Outpatient Clinic at Dr. Mohamad Soewandhie General Hospital over a two-year period, focusing on demographic patterns, clinical stage at diagnosis, and co-infections with other sexually transmitted infections. Methods: A retrospective descriptive study was conducted using medical records of patients diagnosed with syphilis between January 1, 2023, and December 31, 2024. Data collected included age, sex, year of diagnosis, disease stage (primary, secondary, latent), and co-infections (HIV, condyloma acuminata). Result: A total of 55 patients were identified, comprising 42 males (76.4%) and 13 females (23.6%). Most cases (90.9%) occurred in adults aged 19–59 years, with a small proportion in adolescent males (n=5, 9.1%). Latent syphilis predominated (n=39, 70.9%), followed by secondary (n=13, 23.6%) and primary disease (n=3, 5.5%). HIV co-infection occurred in 22 patients (40%), and 11 patients (20%) had concurrent condyloma acuminata, predominantly among males in latent or secondary stages. Conclusion: The findings underscore critical gaps in syphilis screening and management. Integrated, gender-sensitive, and syndemic-informed interventions are urgently required to enhance early detection, reduce transmission, and address co-infection burdens in high-risk populations.